1973
DOI: 10.1139/f73-131
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Comparisons of Day and Night Habits of Freshwater Fish in Ontario Lakes

Abstract: Observations by SCUBA in Georgian Bay and Algonquin Park, Ont., indicate fish have specific habits of diurnal, crepuscular, and nocturnal activity in freshwater lakes. Of 21 species investigated, 17 either schooled or aggregated in the daytime, but only one (Osmerus mordax) schooled at night. The number of fish apparent at night in shallow water was greater than in the daytime primarily because of the influx of offshore species and lack of cover for resting diurnal species. Color changes parallel those reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(102 citation statements)
references
References 0 publications
6
96
0
Order By: Relevance
“…For visually oriented species, decreased activity may lower energetic costs during periods when fish are not actively feeding (Neilson & Perry 1990, Sogard & Olla 1996. Decreased activity may also facilitate the maintenance of congregations when there is insufficient light for visually mediated shoaling (Emery 1973). In addition to this modest light/dark effect, there was also a strong diel pattern of swimming speed, characterized by peak speeds during the early morning, which decreased through the day and then decreased further to uniformly low levels during the night.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For visually oriented species, decreased activity may lower energetic costs during periods when fish are not actively feeding (Neilson & Perry 1990, Sogard & Olla 1996. Decreased activity may also facilitate the maintenance of congregations when there is insufficient light for visually mediated shoaling (Emery 1973). In addition to this modest light/dark effect, there was also a strong diel pattern of swimming speed, characterized by peak speeds during the early morning, which decreased through the day and then decreased further to uniformly low levels during the night.…”
Section: Discussionmentioning
confidence: 99%
“…Although other senses, such as the lateral line system, may play an important role in the spatial and angular orientation of individuals within a school (Partridge & Pitcher 19801, it is unlikely that in the wild many species are capable of schooling in the absence of sufficient light. Thls impression is supported by observational (Emery 1973, Helfman 1979 and bioacoustical studies which generally show that shoals and schools disperse at night (Appenzeller & Leggett 1992, Brodeur & Wilson 1996. Since ambient light in marine and aquatic habitats may vary greatly according to depth, turbidity, season, lunar stage and cloud cover (McFarland 1986), the meaning of 'night', relative to light levels, 1s rather ambiguous.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our simulations, we assumed that wolves primarily detected caribou by olfaction and/or audition because forest cover limits visual detection. Environmental effects on vision may also determine the spatial distribution of prey as it directly affects the benefit of early predator detection provided by groups (Pulliam 1973, Beauchamp 2014 (Emery 1973) and dolphins (Scott and Cattanach 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This dispersal makes fish more easily detected (especially as single targets) by acoustic equipment. Fish also move between offshore and nearshore areas between day and night (e.g., Emery 1973). Masson et al (2001) found that at night, fish distributions were skewed towards the offshore, with a greater proportion of smaller bodied fish present compared with daytime surveys.…”
Section: Figmentioning
confidence: 99%